Pengaruh konfirmasi, persepsi kegunaan, dan persepsi kemudahan terhadap intensi penggunaan kembali mobile banking Bank Sinarmas - Putra, Jo, Anula; Handoyo, Sarwo Edy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The adoption rate of mobile banking services (m-banking) has not reached the expected level, especially in developing countries and customers are less interested in the service. The purpose of the study was to analyze the influence of confirmation and perception of usability on the satisfaction of using Bank Sinarmas mobile banking, the effect of the perception of usability on the intention to reuse Bank Sinarmas mobile banking, the effect of the perception of usability and convenience on the attitude of Bank Sinarmas mobile banking, and the effect of user satisfaction and attitude on the intention to reuse mobile banking Bank Sinarmas. This quantitative study includes the research population of Bank Sinarmas customers who have used mobile banking services. The analysis method uses Partial Least Squares–Structural Equation Modelling (PLS-SEM). From the results of the research and discussion, the conclusions that can be drawn are that confirmation has a positive effect on the satisfaction of using Bank Sinarmas mobile banking, perception of usability has a positive effect on satisfaction with the use of Bank Sinarmas mobile banking, perception of usability has a positive effect on the intention to reuse Bank Sinarmas mobile banking, perception of usability has a positive effect on attitudes towards Bank Sinarmas mobile banking, perception of ease of use has a positive effect on the attitude of Bank Sinarmas mobile banking, user satisfaction has a positive effect on the intention to reuse Bank Sinarmas mobile banking, and attitude has a positive effect on the intention to reuse Bank Sinarmas mobile banking. Tingkat adopsi layanan mobile banking (m-banking) tidak mencapai tingkat yang diharapkan terutama di negara berkembang dan pelanggan kurang berminat terhadap layanan tersebut. Tujuan penelitian untuk menganalisis pengaruh konfirmasi dan persepsi kegunaan terhadap kepuasan penggunaan mobile banking Bank Sinarmas, pengaruh persepsi kegunaan terhadap intensi penggunaan kembali mobile banking Bank Sinarmas, pengaruh persepsi kegunaan dan kemudahan terhadap sikap pada mobile banking Bank Sinarmas, serta pengaruh kepuasan penggunaan dan sikap terhadap intensi penggunaan kembali mobile banking Bank Sinarmas. Penelitian ini kuantitatif dengan populasi penelitian nasabah Bank Sinarmas yang telah menggunakan layanan mobile banking. Metode analisis menggunakan Partial Least Squares–Structural Equation Modelling (PLS-SEM). Dari hasil penelitian dan pembahasan, maka kesimpulan yang dapat diambil adalah konfirmasi berpengaruh positif terhadap kepuasan penggunaan mobile banking Bank Sinarmas, persepsi kegunaan berpengaruh positif terhadap kepuasan penggunaan mobile banking Bank Sinarmas, persepsi kegunaan berpengaruh positif terhadap intensi penggunaan kembali mobile banking Bank Sinarmas, persepsi kegunaan berpengaruh positif terhadap sikap pada mobile banking Bank Sinarmas, persepsi kemudahan penggunaan berpengaruh positif terhadap sikap pada mobile banking Bank Sinarmas, kepuasan penggunaan berpengaruh positif terhadap intensi penggunaan kembali mobile banking Bank Sinarmas, dan sikap berpengaruh positif terhadap intensi penggunaan kembali mobile banking Bank Sinarmas.